Influence of tool shoulder geometry on properties of friction stir welds in thin copper sheets - Galvão, I. (2012)
The aim of this work is to study the influence of the shoulder geometry on friction stir welding of 1 mm-thick copper-DHP plates. The welds were produced using three different shoulder geometries, flat, conical and scrolled, and varying the rotation and traverse speeds of the tool. The flat shoulder tool proved to be inadequate for performing welds, because many defects were produced for all welding conditions. In turn, the scrolled shoulder tool is more effective than the conical one in the production of defect free welds. However, both geometries required a minimum rotational speed to avoid internal defects. For the same welding parameters, greater grain refinement, higher hardness and improved strength are also achieved in the nugget of the welds, using the scrolled tool.